Chlamydia pecorum: fetal and placental lesions in sporadic caprine abortion. (March 2016) - Giannitti, Federico; Anderson, Mark; Miller, Myrna; Rowe, Joan; Sverlow, Karen; Vasquez, Marce; Cantón, Germán
Chlamydial abortion in small ruminants is usually associated with Chlamydia abortus infection. Although Chlamydia pecorum has been detected in aborted ruminants and epidemiological data suggests that C. pecorum is abortigenic in these species, published descriptions of lesions in fetuses are lacking. This work describes fetoplacental lesions in a caprine abortion with C. pecorum infection, and further supports the abortigenic role of C. pecorum in ruminants. A 16-month-old Boer goat aborted twin fetuses at ~130 days of gestation. Both fetuses (A and B) and the placenta of fetus A were submitted for postmortem examination and diagnostic workup. At autopsy, the fetuses had moderate anasarca, intermuscular edema in the hindquarters (A), and brachygnathia and palatoschisis (B). In the placenta, the cotyledons were covered by yellow fibrinosuppurative exudate that extended into the adjacent intercotyledonary areas. Histologically, there was severe suppurative and necrotizing placentitis with vasculitis (arteriolitis) and thrombosis, multifocal lymphohistiocytic and neutrophilic hepatitis (A), and fibrinosuppurative enteritis in both fetuses. Chlamydia antigen was detected in the placenta by the direct fluorescent antibody test and in fetal intestines by immunohistochemistry. Nested polymerase chain reaction of DNA extracted from formalin-fixed, paraffin-embedded sections of placenta and intestine amplified 400 bp of the Chlamydia 16S rRNA gene that was sequenced and found to be 99% identical to C. pecorum by BLAST analysis. Other known abortigenic infectious agents were ruled out by specific testing. It is concluded that C. pecorum infection is associated with fetoplacental lesions and sporadic abortion in goats.